The Influence of Return on Assets, Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Tax Avoidance - Muhammad Nazar Suhada; Fuad Ramdhan Ryanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the connection between financial performance metrics, specifically Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TAT), and tax avoidance behavior among companies listed on the Indonesia Stock Exchange. Using a quantitative analysis approach, the results indicate a significant positive correlation between ROA and tax avoidance, suggesting that more profitable companies are more likely to adopt tax avoidance strategies. On the other hand, the CR is found to have a negative correlation with tax avoidance, implying that firms with stronger liquidity are less inclined to engage in aggressive tax strategies, possibly to preserve their reputation. While DER and TAT do not exhibit a significant impact on tax avoidance, the study underscores the need to consider a broader perspective when examining corporate tax practices. Future research could benefit from exploring qualitative factors that might influence tax avoidance behavior.